Automatic Sorting System Based on Sensors for The Extrusion of Filament Used in 3d Printers Based on Recycled Pet Plastic Bottles - Ingaroca Ames, John Axell (2023)
The problem of the century is environmental pollution, which has a great relationship with plastics that do not reach a proper reuse cycle, from problems such as clogging of sewers in cities to a large increase in the melting of Antarctica, the excess of waste accumulated by plastics has led to seek innovative solutions. Therefore, this article focuses on the design and simulation of a sorting machine and extruder of PET bottles for the manufacture of filament, which will serve as base material for the 3D printer, this means boosting the economy within the regional context, the goal is to implement a new recycling technique to support the environment and improve the quality of life of people. The methodology that develops the study is mainly based on the VDI2221 standard, on the other hand, the type of research is correlational, non-experimental design. Then, the objective of the study focuses on the reuse of plastic bottles from supermarkets in the city of Huancayo. The result obtained is the manufacture of PET filament, which is given by cutting into strips the bottle previously selected by the system, and then, passing to the extrusion phase, obtaining a diameter of 1.7 mm. In conclusion, the prototype was able to manufacture a filament compatible with 3D printers, which is not harmful to people's health, since PET plastic does not emit toxic gases; in addition, it contributes to the care of the environment, by reusing plastic containers. Keywords—Plastic contamination, Filament, 3D Printer